2012
DOI: 10.1136/bjophthalmol-2012-301810
|View full text |Cite
|
Sign up to set email alerts
|

Central serous chorioretinopathy and risk of ischaemic stroke: a population-based cohort study

Abstract: CSCR is an independent indicator for the increased risk of subsequent ischaemic stroke development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
1
23
0
2
Order By: Relevance
“…Haimovici et al 13 reported that uncontrolled systemic hypertension, instead of hypertension, is a risk factor for CSCR. An increased incidence of stroke has been reported in patients with CSCR by Tsai et al 14 In their study, after adjusting for other confounding factors, CSCR is reported to be an independent risk factor for stroke. Tittl et al 11 studied the correlation between CHD and CSCR, in which logistic regression analysis results revealed that CHD is not a statistically significant risk factor for CSCR.…”
Section: Discussionmentioning
confidence: 61%
“…Haimovici et al 13 reported that uncontrolled systemic hypertension, instead of hypertension, is a risk factor for CSCR. An increased incidence of stroke has been reported in patients with CSCR by Tsai et al 14 In their study, after adjusting for other confounding factors, CSCR is reported to be an independent risk factor for stroke. Tittl et al 11 studied the correlation between CHD and CSCR, in which logistic regression analysis results revealed that CHD is not a statistically significant risk factor for CSCR.…”
Section: Discussionmentioning
confidence: 61%
“…These studies suggested that CSCR could be an ocular finding of undefined systemic disease. In fact, it was reported that risk for stroke and coronary artery disease is higher in patients with CSCR compared to the general population in previously performed studies [33,34]. The author proposed that the choroidal vasculopathy observed in CSCR may not be isolated but rather part of a more diffuse deterioration in vascular function that is yet to be better characterized.…”
Section: Discussionmentioning
confidence: 87%
“…As compared to control patients, males with CSCR have a significantly higher rate of coronary heart disease (Hazard Ratio (HR): 1.72), indicating that CSCR may be a potential risk factor for the development of coronary heart disease in men . CSCR was also shown to be an independent risk factor for ischemic stroke (HR: 1.56; 95% confidence interval (CI), 1.11e2.18) (Tsai et al, 2012), and for organic and psychogenic erectile dysfunction (HR: 2.14; 95% CI, 1.34e3.44 and 3.83; 95% CI, 1.47e10.01, respectively) (Tsai et al, 2013b). Consequently, the choroidal vasculopathy described in CSCR may not be isolated but rather part of a more diffuse vascular dysfunction that is yet to be better characterized.…”
Section: Cardiovascular Diseases and Hypertensionmentioning
confidence: 97%